Kedudukan Pengaturan Penyelesaian Sengketa Jaminan Penyedia Jasa Konstruksi Melalui Upaya Administratif - Sayuti, Abdurrahman (Fakultas Hukum Universitas Islam Malang, 2024)
Many state administrative decisions in the field of construction services are detrimental to individuals or civil legal entities between service providers and service providers. This study raises the issue of legal arrangements for construction service provider guarantees based on Indonesian laws and regulations and the position of construction service provider guarantee dispute settlement on administrative efforts. This research is a type of normative juridical research using statutory and conceptual approaches. There is a difference in position where there is a conflict of norms in administrative efforts in construction disputes, namely there is no guarantee imposition in carrying out administrative efforts so there must be an understanding of regulatory policies related to construction services in a positive legal order and the position of regulation of construction services so that regulations do not clash in their application.